Social responsibility shared between state, mining companies and communities. The biopolitic and geoetic reflection - Toledo Gutierrez, Carlos Alberto (2019)
The interdisciplinary reflection on socio-environmental conflicts or known as anti-mining activity in the country, is relevant from the point of view of the importance of the national economy and its relationship with extractive activities in the country. The analysis of the problem from different epistemological perspectives, interpretative or hermeneutics, allows to increase the comprehension and possibilities of solution of socio-environmental conflicts. The issue gained importance when it became apparent in the facts that socio-environmental conflicts have the capacity of political incidence to stop important mining projects, in the context of an increase in investments in mining projects in the years 1995-2012. the theme and the case study of the failed Conga mining project in the Cajamarca region (2012), will validate the importance of a novel interpretative analytical approach from concepts such as biopolitics, geoethics and shared social responsibility, a concept that leads to the recognition of the need for shared social responsibility between the state, mining companies and communities.